Use of finite element analysis in pain perception on flat ridges with various occlusal schemes in complete dentures - David Fatola; Ricca Chairunnisa; Ismet Danial Nasution (Indonesian Journal of Prosthodontic, 2023)
Background: Edentulism is an oral health problem that affects the quality of life because of the loss of equilibrium in the stomatognathic system with impaired mastication. This problem can be more deteriorating in the condition of flat ridges, which increases the stress distribution in the mucosa under masticatory load. Stress distributions that exceed the pressure-pain threshold will result in poor masticatory performance, making it critical to choose the ideal occlusal scheme for such ridge conditions. However, the measurement of stress distribution in the mucosa with various occlusal schemes is challenging for in vivo and in vitro testing because of the inability to represent the complex stomatognathic system. In silico testing using finite element analysis (FEA) can be the solution since the modeling simulation is acquired from CT-scan or digital designs and feasible experimental treatments.Objectives: This paper discusses the use of FEA in the measurement of stress distribution in the mucosa, particularly the flat ridges to different occlusal schemes in complete dentures, and its association with pain. Conclusion: The advantages of FEA in obtaining accurate modeling and testing flexibility allow the measurement of stress distribution and its association with pain on flat ridges with different occlusal schemes in complete dentures.